Potential therapeutic role of SIRT1 in age- related hearing loss - Zhao, Tingting; Tian, Guangyong (Frontiers in Molecular Neuroscience, 2022)
Age-related hearing loss (ARHL) is a major public health burden worldwide that profoundly affects the daily life of elderly people. Silent information regulator 1 (SIRT1 or Sirtuin1), known as a regulator of the cell cycle, the balance of oxidation/antioxidant and mitochondrial function, has been proven to have anti-aging and life-extending effects, and its possible connection with ARHL has received increasing attention in recent years. This paper provides an overview of research on the connection between SIRT1 and ARHL. Topics cover both the functions of SIRT1 and its important role in ARHL. This review concludes with a look at possible research directions for ARHL in the future.